Molecular and histological correlates of cognitive decline across age in male C57BL/6J mice. Issue 9 (15th August 2022) - Britton, Rachel; Liu, Angela T.; Rege, Sanket V.; Adams, Julia M.; Akrapongpisak, Lily; Le, David; Alcantara‐Lee, Raniel; Estrada, Raul A.; Ray, Rebecca; Ahadi, Sara; Gallager, Ian; Yang, Cindy F.; et al.
Abstract: Introduction: Increasing age is the number one risk factor for developing cognitive decline and neurodegenerative disease. Aged humans and mice exhibit numerous molecular changes that contribute to a decline in cognitive function and increased risk of developing age‐associated diseases. Here, we characterize multiple age‐associated changes in male C57BL/6J mice to understand the translational utility of mouse aging. Methods: Male C57BL/6J mice from various ages between 2 and 24 months of age were used to assess behavioral, as well as, histological and molecular changes across three modalities: neuronal, microgliosis/neuroinflammation, and the neurovascular unit (NVU). Additionally, a cohort of 4‐ and 22‐month‐old mice was used to assess blood‐brain barrier (BBB) breakdown. Mice in this cohort were treated with a high, acute dose of lipopolysaccharide (LPS, 10 mg/kg) or saline control 6 h prior to sacrifice followed by tail vein injection of 0.4 kDa sodium fluorescein (100 mg/kg) 2 h later. Results: Aged mice showed a decline in cognitive and motor abilities alongside decreased neurogenesis, proliferation, and synapse density. Further, neuroinflammation and circulating proinflammatory cytokines were increased in aged mice. Additionally, we found changes at the BBB, including increased T cell infiltration in multiple brain regions and an exacerbation in BBB leakiness following chemical insult with age. There were also a number of readouts that were unchanged with age and have limited utility as markers of aging in male C57BL/6J mice. Conclusions: Here we propose that these changes may be used as molecular and histological readouts that correspond to aging‐related behavioral decline. These comprehensive findings, in the context of the published literature, are an important resource toward deepening our understanding of normal aging and provide an important tool for studying aging in mice. Abstract : We identify robust molecular and histological changes with age in male C57BL/6J mice that may be used as correlates of aging‐related cognitive decline. These comprehensive findings, in the context of the published literature, are an important resource towards deepening our understanding of normal aging and provide an important tool for studying aging in mice.